Literature Review: Hubungan Tingkat Pengetahuan, Motivasi dan Sikap terhadap Tindakan Tidak Aman (Unsafe Action) pada Tenaga Kerja - Putri, Marisa Adilla; Fatah, Mohammad Zainal (Universitas Airlangga, 2024)
Background: The National Safety Council (NSC) in 2011 stated that 88% of occupational accidents can caused by unsafe behavior. unsafe actions are actions that has dangerous actions of workers that may be set back by various causes. Behavioral factors play a very important role in the occurrence of work accidents. Objectives: This study aims to understand the relationship between knowledge, attitude, and motivation with unsafe behavior in labor. Methods: This study used the literature method of topic-related articles with keywords of knowledge, attitude, motivation, and safe behavior on Google Scholar and PubMed databases. Results: The results of an article search on the Google Scholar and PubMed databases show that there are 6 journals that match the exclusion and inclusion criteria, published between 2018 and 2023. All studied articles are Indonesian-language articles with quantitative research types that use chi-square bivariate test analysis. Conclusions: Based on 6 studies of articles used, there was found to be a relationship between knowledge, attitude, and motivation and unsafe actions in labor.